2002
DOI: 10.1055/s-2002-20255
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Modulation of Telomerase Activity, Telomere Length and Cell Cycle in MKN45 Cells by Verbascoside

Abstract: Screening of natural products with anti-tumor activity as telomerase inhibitor is a new subject in the field of tumor therapy. Using telomerase PCR ELISA, telomere DNA hybridization and flow cytometry analysis, the effects of verbascoside, a phenylpropanoid glucoside extracted from Pedicularis striata Pall, on telomerase activity, telomere length and cell cycle of human gastric carcinoma cells MKN45 was examined in vitro. After being treated with a 50 % inhibition concentration of verbascoside (17.8 microg/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 6 publications
3
26
0
Order By: Relevance
“…Pedicularioside G has anti-angiogenic, antitumour growth, antimetastatic and antitumoural effects. Our previous studies have shown that another phenylpropanoid glycoside, verbascoside (acteoside) extracted from Pedicularis species could reverse malignant phenotypic characteristics, induce tumour cell re-differentiation [27], inhibit telomerase activity and shorten telomere length of human gastric adenocarcinoma cells [28]. The present study further demonstrated that pedicularioside G remarkably decreased the angiogenesis and tumourigenesis.…”
Section: Discussionsupporting
confidence: 73%
“…Pedicularioside G has anti-angiogenic, antitumour growth, antimetastatic and antitumoural effects. Our previous studies have shown that another phenylpropanoid glycoside, verbascoside (acteoside) extracted from Pedicularis species could reverse malignant phenotypic characteristics, induce tumour cell re-differentiation [27], inhibit telomerase activity and shorten telomere length of human gastric adenocarcinoma cells [28]. The present study further demonstrated that pedicularioside G remarkably decreased the angiogenesis and tumourigenesis.…”
Section: Discussionsupporting
confidence: 73%
“…It has been confirmed that the highest rate of telomerase activity is at S phase, whereas the lowest is at the G2/M phase [23]. Thus, our data indicate that the G2/M phase blockage is largely responsible for the antisense gene-mediated down-regulation of telomerase activity, which is in agreement with results from previous investigations [24][25][26].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the chemical characterization by HPLC/UV of Stachytarpheta cayennensis extracts revealed higher amounts of iridoid than arylpropanoid in the ethanolic extract SC01, whereas in the extract SC02, arylpropanoid was predominant over iridoid. The arylpropanoid verbascoside (also called acteoside) is found in several species in the Verbenaceae family (Cometa et al, 1993), and has been shown to present a wide range of biological activities (Akbay et al, 2002;Sheng et al, 2002;Zhang et al, 2002). Indeed, Schapoval et al (1998) demonstrated an important anti-inflammatory activity of verbascoside isolated from Stachytarpheta cayennensis.…”
Section: Discussionmentioning
confidence: 99%